2021
DOI: 10.1136/bmjgh-2020-003257
|View full text |Cite
|
Sign up to set email alerts
|

The role of governance in implementing sustainable global health interventions: review of health system integration for integrated community case management (iCCM) of childhood illnesses

Abstract: Improving health outcomes in countries with the greatest burden of under-5 child mortality requires implementing innovative approaches like integrated community case management (iCCM) to improve coverage and access for hard-to-reach populations. ICCM improves access for hard-to-reach populations by deploying community health workers to manage malaria, diarrhoea and pneumonia. Despite documented impact, challenges remain in programme implementation and sustainability. An analytical review was conducted using ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Especially, the problem would be very serious in the case of a rural community, which is the typical characteristic of our study population. Such challenges are also recently documented in a global review [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially, the problem would be very serious in the case of a rural community, which is the typical characteristic of our study population. Such challenges are also recently documented in a global review [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional work also needs to be done to understand whether and how community engagement and improved healthcare systems can ultimately reduce inequities (29). Providing equitable access, of course, requires that healthcare systems have adequate infrastructure, governance, personnel, and other resources (17). This includes strong partnerships, and good program management/coordination, to ensure success and sustainability (17).…”
Section: Integrated Clinical Carementioning
confidence: 99%
“…Providing equitable access, of course, requires that healthcare systems have adequate infrastructure, governance, personnel, and other resources (17). This includes strong partnerships, and good program management/coordination, to ensure success and sustainability (17). A strong health system requires multi-sectoral engagement at many levels, including a community-based system for accessing local healthcare services (17).…”
Section: Integrated Clinical Carementioning
confidence: 99%
See 1 more Smart Citation
“…Lack of access to timely and appropriate clinical management of sick children is a key factor driving poor health outcomes (3,4) prompting a World Health Organisation/UNICEF joint statement in 2012 advocating for integrated community case management (iCCM) of malaria, diarrhoea and pneumonia delivered by community-based lay health workers, who would be trained to diagnose and treat key childhood conditions in areas with poor access to facility-based services (3). In the decade following this statement, iCCM programmes have been introduced into more than 50 low-and middle-income countries (LMICs) (5)(6)(7). Whilst a recent multi-country modelling study in DRC, Malawi, Niger, and Nigeria (8) estimated that iCCM may have been responsible for averting nearly 5000 deaths per year in these countries combined due to malaria, diarrhoea and pneumonia, this estimate varied considerably between countries, and was in contrast to a Cochrane systematic review which found no clear impacts of iCCM on morbidity and mortality (9).…”
Section: Introductionmentioning
confidence: 99%